Does foreign aid reduce migration? - Andreas Fuchs; André Gröger; Tobias Heidland; Lukas Wellner (Kiel Institute for the World Economy (IfW Kiel), 2023)
The widespread use of foreign aid to address the "root causes" of irregular migration lacks a robust empirical foundation. In a new study (Fuchs, A., A. Groeger, T. Heidland, and L. Wellner (2023). The Effect of Foreign Aid on Migration: Global Micro-Evidence from World Bank Projects. Kiel Working Paper 2257) that we summarize here for a wider audience, we provide the first comprehensive causal analysis that examines micro-level evidence across all developing countries that received assistance from the World Bank between 2008 and 2019. Our analysis is the first to disentangle the impacts of foreign aid on various aspects of migration: individuals' aspirations, capabilities, and actual migration patterns. In alignment with the notion of utilizing aid to mitigate the root causes of irregular migration, our study reveals that the announcements and disbursements of new aid projects significantly reduce people's migration aspirations. This effect is temporary in nature and is notably absent in fragile countries. Over the longer term, the critical factor is whether aid ultimately enhances living conditions. Our findings provide some evidence supporting this, as improvements in living conditions bolster individuals' capabilities. This can lead to increased migration, yet the notable difference is that these individuals tend to follow regular channels for migration. These findings hold substantial significance for policymakers and those involved in foreign aid allocation that we discuss towards the end of this policy brief. – – Der weit verbreitete Einsatz von Entwicklungshilfe zur Bekämpfung von "Fluchtursachen" oder, präziser formuliert, irregulärer Migration, entbehrt einer soliden empirischen Grundlage. In einer neuen Studie (Fuchs, A., A. Groeger, T. Heidland, and L. Wellner (2023). The Effect of Foreign Aid on Migration: Global Micro-Evidence from World Bank Projects. Kiel Working Paper 2257), die wir hier für ein breiteres Publikum zusammenfassen, liefern wir die erste umfassende Kausalanalyse, die Evidenz auf Mikroebene für alle Entwicklungsländer untersucht, welche zwischen 2008 und 2019 von der Weltbank unterstützt wurden. Unsere Analyse ist die erste, die die Auswirkungen der Entwicklungshilfe auf verschiedene Aspekte der Migration aufschlüsselt: die Aspirationen, Möglichkeiten (sog. Capabilities) zur Migration und tatsächlicher Migration. Im Einklang mit der Idee, dass Entwicklungshilfe die Ursachen der irregulären Migration reduziert, zeigt unsere Studie, dass die Ankündigung und Umsetzung von Entwicklungshilfeprojekten die Migrationsaspirationen von Menschen in Empfängerländern deutlich reduziert. Dieser Effekt ist vorübergehender Natur und tritt nicht in fragilen Ländern auf. Für die langfristige Betrachtung des Effekts von Entwicklungshilfe auf Migration ist der entscheidende Faktor, ob Entwicklungshilfe letztlich die Lebensbedingungen verbessert, was jedoch auch Migrationsmöglichkeiten verbessern kann. Unsere Ergebnisse liefern einen Beleg dafür, dass dies der Fall ist. Wichtig anzumerken ist jedoch, dass zusätzliche Migration in regulären Kanälen stattfindet. Diese Ergebnisse sind für politische Entscheidungsträger von erheblicher Bedeutung, wie wir am Ende dieses Beitrags erläutern.
Additional information: German version available: https://hdl.handle.net/10419/279516
Keywords: 330; Migration; Foreign Aid; Root causes; Irregular migration; Refugees; Asylum; Development; Migration; Entwicklungshilfe; Fluchtursachen; Irreguläre Migration; Flüchtlinge; Asyl; Entwicklung